Editor's foreword - Vadim Radaev (Journal of Economic Sociology, 2019)
Dear colleagues,As it has been announced, the Journal of Economic Sociology is developing a new rubric, ‘Debates’. Two extended polemic responses are presented in this issue. The first paper presents a critical view of Rostislav Kapelyushnikov’s essay on the legacies of Max Weber. The second paper is a critical response to the text of Roman Bumagin and Dmitry Rogozin on the survey approach.